Copper‐Catalyzed Trifunctionalization of Alkynes: Rapid Formation of Oxindoles Bearing Geminal Diboronates. Issue 4 (13th December 2018) - He, Tao; Li, Bin; Liu, Li‐Chuan; Wang, Jing; Ma, Wen‐Peng; Li, Guang‐Yu; Zhang, Qing‐Wei; He, Wei
Abstract: A copper‐catalyzed trifunctionalization of alkynes that provides rapid access to oxindoles bearing a geminal diboronate side chain, highlighted by the simultaneous formation of one C−C bond and two C−B bonds, is reported. This new reaction features simple reaction conditions (ligand‐free catalysis), a general substrate scope, and excellent chemoselectivity. Mechanistic study revealed a reaction sequence constituted by, in the order, borylation, intramolecular cross‐coupling, hydroboration, which has been rarely documented. Abstract : A ligand‐free Cu I ‐catalyzed trifunctionalization of 2‐ynamide was developed, which provides rapid access to oxindoles bearing a geminal diboronate substitution on the side chain. The new reaction features simple reaction conditions, a general substrate scope and excellent chemoselectivity.